GAMBARAN FAKTOR- FAKTOR RESILIENSI PADA REMAJA PEREMPUAN YANG TINGGAL DI PANTI ASUHAN - Akasya Shintaningtyas; Dhevy Setya Wibawa (MANASA, 2020)
Teenagers have various problems including those who live in orphanages for various reasons.This situation can cause them to encounter various problems from their inner side and theenvironment such as, resignation due to lack of attention from their closest person,withdrawing from the society, facing the challenges feels heavy, difficult to be open with thesurrounding community especially after they leave the orphanage and this often happens toadolescents women. However, there are young women who are able to turn these negativeconsequences into challenges to get up and develop themselves in a positive direction. Thisqualitative study uses a semi-structured interview which aims to look at the factors of resilienceof adolescent girls living in orphanages in terms of Grotberg's theory, among others, thefactors I Am, I Can and I Have with three female teenage participants who have a minimum ofone year of living in orphanage. The results of this study indicate that the factors I Have(environmental support), I Am (self-strength) and I Can (social and interpersonal) are relatedto each other, although in factor I Can there are some young women who still have highemotions but they has been able to control his emotions thanks to the support and assistancefrom the surrounding environment which can be the strength of self to determine future lifegoals.